1994
DOI: 10.1148/radiology.190.1.8259424
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal amyloidosis: radiologic features by chemical types.

Abstract: Characteristic radiographic changes of each chemical type of amyloid protein can be detected well in the small intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 0 publications
4
15
0
4
Order By: Relevance
“…Our findings with CT agree with reports of barium studies that have described bowel wall thickening as a common abnormality in GI amyloidosis [4]. We also agree with radiologic [4] and autopsy [6] studies that have found the small bowel to be the most common site of involvement.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings with CT agree with reports of barium studies that have described bowel wall thickening as a common abnormality in GI amyloidosis [4]. We also agree with radiologic [4] and autopsy [6] studies that have found the small bowel to be the most common site of involvement.…”
Section: Discussionsupporting
confidence: 91%
“…Tada et al [4] reported that fold thickening in AL is due to interstitial, not to vascular, involvement. They also reported that AL and AA have different appearances on enteroclysis, with AL more likely to produce polypoid defects [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The reported preferential types and locations of amyloid deposits are associated with the type of amyloid fibril protein (6,7). The AA type of amyloid protein is deposited mainly in the lamina propria mucosa of the GI tract.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous reports, small bowel is the most commonly involved organ in the gastrointestinal system (15,16). The most frequent imaging finding of small intestinal amyloidosis is regular thickening of the folds (focal or diffuse), which displays edema due to ischemia as a result of vascular accumulation.…”
Section: Radiologic Featuresmentioning
confidence: 99%